2007
DOI: 10.1159/000109396
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Cytokines and Steroid Responsiveness in Idiopathic Nephrotic Syndrome of Childhood

Abstract: Background/Aim: Steroid-resistant nephrotic syndrome (SRNS) has been associated with activation of TGF-β1 and progression to chronic kidney disease. Steroid-sensitive nephrotic syndrome (SSNS) has been associated with activation of T-cells and favorable outcome. Our objective was to distinguish SRNS from SSNS and focal segmental glomerulosclerosis (FSGS) from minimal change disease (MCD) on the basis of urinary cytokine profile. Method: We used a high-throughput cytokine array. ICAM-1 and TGF-β Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Major limitations of that study are that (1) the peptides in the signature were not identified, and (2) proteomic signatures have limited clinical value due to the lack of availability of affordable and practical testing procedures. A later attempt was made to determine if a urinary cytokine panel could distinguish steroid responsiveness in pediatric idiopathic NS [25]. While the authors demonstrated that a high-throughput cytokine array, including ICAMI, could distinguish patients with NS from controls, it did not differentiate steroid responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Major limitations of that study are that (1) the peptides in the signature were not identified, and (2) proteomic signatures have limited clinical value due to the lack of availability of affordable and practical testing procedures. A later attempt was made to determine if a urinary cytokine panel could distinguish steroid responsiveness in pediatric idiopathic NS [25]. While the authors demonstrated that a high-throughput cytokine array, including ICAMI, could distinguish patients with NS from controls, it did not differentiate steroid responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Increased urinary TGF-beta is detected in patients with some forms of nephrotic syndrome (6), IgA nephropathy (7), and focal segmental glomerulosclerosis (FSGS) (7, 8). Interestingly, while detection of TGF-beta in the urine can differentiate between FSGS and the non-fibrotic process of minimal change disease (8), TGF-beta levels cannot be used predict response to corticosteroid therapy, despite the fact that some anti-fibrotic treatments may reduce these levels (9). In human FSGS (10) and in experimental models of renal fibrosis (11), TGF-beta is closely associated with ECM accumulation.…”
Section: Tgf-beta and The Pathogenesis Of Chronic Kidney Diseasementioning
confidence: 99%
“…For instance, CCL2/MCP-1 and CXCL8/IL-8 are the chemokines more commonly associated with pediatric renal diseases [7,11,12,15,16,19,20,46,47,55,58,[65][66][67][68][69][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…Araya and coworkers evaluated 23 patients with MCNS and 8 healthy controls and detected that MCNS patients have impaired T regulatory cells with low levels of IL-10 [8]. Woroniecki and coworkers studying 24 children with INS reported that urinary levels of the fibrogenic cytokine TGF-might differentiate between FSGS and MCNS, but it seemed not to be a biomarker of steroid responsiveness [46]. Our research group measured plasma and urinary chemokines in 32 children with INS divided according to steroid responsiveness into 12 healthy controls [7].…”
Section: Chemokines In Glomerular Diseasesmentioning
confidence: 99%